Pelatihan Membuat Money Bouquet Untuk Meningkatkan Wawasan dan Keterampilan Ibu-Ibu Rumah Tangga di Lingkungan Desa Sumbertempur Kabupaten Malang - Indah Martha Fitriani; Agus Dwi Putra; Erlillah Rizqi Kusuma Pradani; Luchyto Chandra Permadi; Yayi Febdia Pradani; Muhammad Rizal Akbar Zamzami; Muhammad Ana Zamzami; Dedi Romadon (I-Com: Indonesian Community Journal, 2023)
Sumbertempur village is a village in Wonosari District. This village consists of several hamlets totaling four. One of the hamlets that was used as the object of training was Tempursari Kulon hamlet. The distance between the combat source and the district is relatively close, around 4 km. Meanwhile, the distance from Sumbertempur to the center of the district capital is around 37 km. This situation encourages the author to carry out outreach and training in the business sector so that residents there have additional income. The training was a training on making money bouquets using the learning by doing method and the number of participants was 10 residents (mothers) and 7 students. The results of the work made money bouquets run smoothly and this activity produced 10 money bouquets. The mothers also had high enthusiasm in attending this activity.